Tranexamic acid for trauma:: narrative review - Martinez, Gabriel; Flávio Meirelles Marchini, Júlio; Adão Fanti Silva, Diego (LAJEC - Latin American Journal of Emergency Care, 2024)
Trauma is one of the main causes of death and disability worldwide. One of the main treatments for this situation is the infusion of tranexamic acid in patients with trauma-induced coagulopathy or even traumatic brain injury. We discuss the evidence on the use of this drug in trauma patients with the conditions described. Thus, this narrative review aimed to point out the results, divergences and new perspectives of the main studies and new recommendations related to tranexamic acid infusion in patients with trauma-induced coagulopathy and traumatic brain injury.